Kebijakan Hukum Pelecehan Seksual (CatCalling) dalam Persektif Hukum Pidana di Kabupaten Karawang - Dzakiyah Noor Mughni; Hana Faridah (Peneliti.net, 2023)
This study discusses harassment law policies from a criminal law perspective. The purpose of this research is to analyze the regulation of catcalling that is often done by the community. This research uses juridical-empirical analysis. The results of this study indicate that someone who commits sexual harassment has the potential to be a criminal act both verbally and is examined by several articles in the Criminal Code. Because there are legal regulations that apply in Indonesia regarding sexual harassment, it is hoped that there will be a paradigm shift in social society dealing with views and assumptions about women victims of sexual harassment. In order to achieve a clear determination that there is a legal policy to regulate sexual harassment regulations regarding catcalling and there are sanctions for perpetrators who do catcalling.